Kontribusi Biomassa dari Daun Gugur dalam Penyediaan Hara pada Pertanaman Ubi Kayu - Suwarto Sukiman; Ahmad Faris Abrori (Universitas Trunojoyo Madura, 2018)
In the central area of production, cassava is cultivated continuously along the year as monoculture. At harvest time a number of biomass will be transported from the land in the form of cassava roots, stem, and leaves; a number of nutrient transported from the land. However, the cassava is still could be cultivated with not significantly decreasing its productivity. Probable that is related to the leaves fall during the planting season as the biomass return. The study to know the contribution of the leaves fall to nutrient supply of cassava field has been conducted by planting cassava varieties of Adira-1, Gajah and Mangu as monoculture and intercropped with yam bean. The leaves were starting fall at 8 weeks after planting (WAP). The contribution of the leaves fall was significantly different among the varieties. The influence of planting system was not significant to the leaves fall. Up to the harvest time at 34 WAP, the nutrient supply of leaves fall of Adira-1 was estimated could replace all nutrient of N, P, K, Ca and Mg transported in the roots of 15.7 ton ha-1. The leaves fall of Gajah varieties was estimated could replace all nutrient of N and Ca transported in the roots of 19.6 ton ha-1. However, the leaves fall of Mangu variety was estimated could not replace all nutrient of N, P, K, Ca and Mg transported in the roots of 30.5 ton ha-1. Additional fertlizers were needed to supply enought nutrient to Gajah and Mangu varieties.